AB0717 Clinical Characteristics of Ankylosing Spondyloarthritis in Real Clinical Practice in Russia: Results of A Single Multicenter Non-Interventional Study – Epika 2. (15th July 2016) - Dubinina, T.; Erdes, S.; Rumyantseva, O.; Abdulganieva, D.; Vinogradova, I.; Evstigneeva, L.; Yelonakov, A.; Otteva, E.; Raskina, T.; Salnikova, T.; Samigullina, R.; Sorotskaya, V.; et al.
Abstract : Objectives: Recognizing the clinical picture of ankylosing spondylitis (AS) in real practice would help to optimize healthcare services provided to this group of pts. Methods: A single multicenter non-interventional study was conducted in spring 2015 y in order to ascertain the clinical features of AS in the real practice of a rheumatologist. 402 consecutive AS pts (meeting modified N-Y criteria) referred to a rheumatologist were evaluated following accepted standards during 2 mo at 10 clinical centers of Russia. All pts were evaluated, including those who addressed because of deterioration, and pts coming for regular check-ups within the disease monitoring. Results: Patients' mean age was 40, 8±11, 5 y, . 292 (72, 6%)- males, 82, 6% were HLA-B27- positive. Age at AS onset was 27, 6±12, 3 y., in 65, 4% AS onset occurred before the age of 30 y.o., and in 16, 9% – before 16 y.o. Time to establishing the AS diagnosis was 85, 2±86, 2 mo. By the moment of evaluation inflammatory back pain was present in 55, 7% pts, peripheral arthritis - in 33, 1%, enthesitis – in 37, 1%, dactylitis – in 1, 2%. Average BASDAI disease activity score was 4, 3±2, 1 (in 54, 2% of pts it was >4, in 12, 7% - >7, and in 18, 2% - <2), and BASFI score – 4, 1±1, 8 (in 48, 0% of pts it was >4, in 17, 1%, - >7, and in 26, 1% - <2). Extraskeletal manifestations were documented in 13, 2% AS pts (including uveitis – in 45, 3%, psoriasis – in 28, 3%, Chrons disease – in 7, 5%, IgA-associated neuropathy – in 5, 7%, aortitis – in 3, 8%). Such complications as amyloidosis were registered in 6 (1, 5%) pts, cardiac arrhythmias – in 10 (2, 5%) pts, aortal defect – in 1 (0, 2%) patient. Most common comorbidities (verified by corresponding specialists) in this population were: arterial hypertension - in 25, 1% AS pts, gastric ulcer – in 9, 7%, ischemic heart disease – in 4, 0%, diabetes mellitus – in 3, 0%, chronic bronchitis – in 2, 2%, bronchial asthma – in 2, 0%, HCV hepatitis – 1, 7%, HBV hepatitis – in 1, 5%, tuberculosis – in 1, 0%, oncologic diseases – in 0, 2%, demyelinating conditions – in 0, 2% pts. Comorbidities were not found in more than 50% (52%) of pts. Total arthroplasty procedures were documented in 19 (4, 7%) pts, including 15 (3, 7%) cases of hip replacement, and knee replacement in the rest. By the moment of evaluation another 6, 7% of pts required total hip replacement procedure. 92% of pts were taking NSAIDs, sulfasalazine – 31, 2%, methotrexate – 11, 2%, peroral GCs s - 9, 3%, TNF-α inhibitors– 19, 1%. Conclusions: In real clinical practice the final AS diagnosis is usually established in more than 7 years after AS onset, by that moment the disease has already reached high activity and pronounced functional impairments occurred. Various comorbidities are found in >40% of AS pts, but with much lower incidence as compared to other systemic rheumatoid diseases. Disclosure of Interest: None declared